Analysis of a standing wave thermoacoustic engine with multiple unit stages - Murti, Prastowo; Setiawan, Ikhsan; Rosafira, Jihan Zeinyuta; Widyaparaga, Adhika; Astuti, Wijayanti Dwi; Biwa, Tetsushi (Center of Biomass & Renewable Energy (CBIORE), 2024)
The thermoacoustic engine is an eco-friendly technology capable of harnessing solar and waste energy for electricity generation, in conjunction with a linear alternator, and can function as a heat pump. This engine type holds significant appeal due to its simplistic design, devoid of any mechanical moving components, comprising only a stack sandwiched between heat exchangers within a resonator. When the temperature gradient across the stack reaches the critical threshold (onset temperature), the working gas undergoes spontaneous oscillation. Typically, a high onset temperature is necessary to induce gas oscillation in a thermoacoustic engine due to viscous losses within the system. A method to lower the onset temperature by increasing the number of unit stages consisting of stacks and heat exchangers so that the engine can utilize low-grade thermal sources has been developed to overcome this challenge. However, this method has only been applied to traveling-wave thermoacoustic engines. Its application in standing-wave engines, which offer a more compact and straightforward structure, remains unexplored. This research aims to examine how the number of unit stages in a standing-wave thermoacoustic engine influences the onset temperature and acoustic field. The onset temperature is estimated using a fundamental hydrodynamics equation and the investigation of the acoustic field throughout the engine using DeltaEC software. Results showed that the strategic positioning of multiple unit stages is essential to achieve a low onset temperature. The minimum onset temperature, approximately 92°C, is obtained when three- or four-unit stages are installed. Additionally, increasing the number of unit stages does not affect the acoustic impedance and phase difference between pressure and velocity in the stack, while simultaneously enhancing both acoustic power output and thermal efficiency.